2021
DOI: 10.1002/cmdc.202100642
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Mitochondria with Mutant DNA through Extracellular Vesicles Helps Cancer Cells Acquire Chemoresistance

Abstract: Triple negative breast cancer (TNBC) is one of the most aggressive subtypes of breast cancer with the worst prognosis after chemo‐ or radiation therapy. This is mainly due to the development of cancer chemoresistance accompanied by tumor recurrence. In this work, we investigated a new mechanism of acquired chemoresistance of TNBC cells. We showed that extracellular vehicles (EVs) of chemoresistant TNBC cells can transfer mitochondria to sensitive cancer cells, thus increasing their chemoresistance. Such transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…A recent study demonstrated that TNBC-EVs derived from chemo-resistant cells increase chemoresistance in chemo-sensitive cancer cells by transferring mitochondria with mutations in the MT-ND4 gene [ 95 ]. MT-ND4 encodes an NADH-ubiquinone oxidoreductase chain 4 protein, one of seven components of the respiratory complex I.…”
Section: Tnbc-evsmentioning
confidence: 99%
“…A recent study demonstrated that TNBC-EVs derived from chemo-resistant cells increase chemoresistance in chemo-sensitive cancer cells by transferring mitochondria with mutations in the MT-ND4 gene [ 95 ]. MT-ND4 encodes an NADH-ubiquinone oxidoreductase chain 4 protein, one of seven components of the respiratory complex I.…”
Section: Tnbc-evsmentioning
confidence: 99%
“…Circulating mtDNA‐rich EVs were found in insulin therapy‐antagonized metastatic breast cancer patients, which might act as a pro‐oncogenic signal to induce endocrine therapy resistance in oxidative phosphorylation‐dependent breast cancer cells (Sansone et al., 2017 ). EVs released by chemoresistant triple‐negative breast cancer cells could deliver functional mitochondria to sensitive triple‐negative breast cancer cells, leading to increased chemoresistance and tumorigenesis (Abad & Lyakhovich, 2022 ). Likewise, EVs from tumour‐activated stromal cells delivered mitochondria to malignant glioma cells, resulting in resistance to cancer radiotherapy and chemotherapy (Salaud et al., 2020 ).…”
Section: Pathological Effects Of Mitoevsmentioning
confidence: 99%
“…In a similar study, Thomas et al [ 228 ] reported that MSCs are able to package functional mitochondria into extracellular vesicles that can be transferred to chondrocytes without direct intercellular interactions. A new mechanism of acquired chemoresistance of triple-negative breast cancer cells by the EV-mediated transfer of mitochondria was shown by Abad et al [ 229 ]. On the other hand, an interesting study by Crewe et al [ 230 ] demonstrated that the injection of EVs released by stressed adipocytes and containing oxidatively damaged mitochondrial particles may have, contrary to expectations, a positive effect and alleviate cardiac ischemia in mice, representing a first example of interorgan mitohermesis in vertebrates.…”
Section: Membrane Protrusions: Cytonemes Tunneling Nanotubes and Inte...mentioning
confidence: 99%